Modified PVDF-HFP / PEO composite solid electrolyte membrane and preparation method thereof

By adding sulfonated nickel phthalocyanine filler SCNC to the PVDF-HFP three-dimensional fiber framework and combining it with PEO, the problem of insufficient mechanical strength and ionic conductivity of PEO-based solid electrolyte membrane is solved, and better comprehensive performance is achieved.

CN119674207APending Publication Date: 2025-03-21HEBEI UNIV OF ENG

Patent Information

Application Number
CN202411856291.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing PEO-based solid electrolyte membranes have shortcomings in terms of mechanical strength, stability and ionic conductivity, and it is difficult to effectively improve their comprehensive performance.

Method used

The preparation method of the modified PVDF-HFP/PEO composite solid electrolyte membrane is adopted. By adding sulfonated nickel phthalocyanine filler SCNC to the PVDF-HFP three-dimensional fiber framework and combining it with PEO, the mechanical strength and ionic conductivity of the electrolyte membrane are improved.

Benefits of technology

It significantly improves the mechanical strength, stability and ionic conductivity of the PEO composite solid electrolyte membrane, and improves its compatibility with lithium anode and high-voltage electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674207A_ABST
    Figure CN119674207A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a modified PVDF-HFP / PEO composite solid electrolyte membrane, which comprises the following steps: doping a spinning solution of PVDF-HFP by using a sulfonated nickel phthalocyanine (at) cobalt-graphite carbon nitride composite material CNC as a filler, preparing a CNC filler doped PVDF-HFP three-dimensional fiber skeleton by using an electrostatic mode process, and preparing a PVDF-HFP / PEO composite solid electrolyte membrane by using the CNC filler doped PVDF-HFP three-dimensional fiber skeleton. The solid-state electrolyte membrane is obtained by compounding the three-dimensional fiber skeleton and a PEO-LiTFSI membrane casting solution, so that the mechanical strength and stability of the solid-state electrolyte membrane (diaphragm) are improved, the volume change in the electrochemical reaction process can be effectively buffered, the lithium dendrite growth resistance of the solid-state electrolyte membrane is improved, and the electrochemical properties such as ionic conductivity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a modified PVDF-HFP / PEO composite solid electrolyte membrane and a preparation method thereof. Background Art

[0002] Polyethylene oxide (PEO) is a commonly used solid electrolyte material, especially widely used in lithium-ion batteries and sodium-ion batteries. PEO-based solid electrolyte membranes have attracted attention due to their good flexibility, easy processing and relatively high ionic conductivity. PEO solid electrolyte membranes have good flexibility and mechanical properties and are suitable for making thin films. PEO can be easily processed into thin films by solution casting, melt extrusion and other methods. However, existing PEO-based solid electrolyte membranes still have some shortcomings, such as insufficient mechanical strength and stability, poor resistance to the growth of lithium dendrites, and low ionic conductivity due to the high crystallinity of PEO. Therefore, the ionic conductivity of PEO solid electrolytes needs to be further improved.

[0003] In order to improve the mechanical strength of PEO-based solid electrolyte membranes, prior art such as CN116247291A discloses that inorganic particles SiO2 microspheres, nano-ceramic particles LLZTO, LLZO, and TiO2 are used as fillers to modify PEO-based solid electrolyte membranes. On the one hand, inorganic particles form physical crosslinking points in the polymer matrix to increase the rigidity and tensile strength of the material. On the other hand, they are used to interfere with the crystallization process of PEO, reduce the crystallinity of PEO, and increase the proportion of amorphous regions, thereby improving the overall conductivity. However, their conductivity-enhancing effects on PEO-based solid electrolyte membranes are still not ideal. Prior art such as CN116365054B also discloses that metal phthalocyanines such as nickel phthalocyanine are doped into solid electrolyte membranes, and the metal atoms in the phthalocyanine molecules interact with lithium ions to form more ion hopping paths, thereby improving ionic conductivity; however, nickel phthalocyanine is difficult to disperse evenly in PEO and is prone to agglomeration, which affects the mechanical properties of the electrolyte membrane due to the agglomeration of metal phthalocyanines. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for preparing a modified PVDF-HFP / PEO composite solid electrolyte membrane, which can effectively improve the mechanical strength, stability and ionic conductivity of the composite membrane, and obtain a PEO composite solid electrolyte membrane with better comprehensive performance.

[0006] (II) Technical solution

[0007] A method for preparing a modified PVDF-HFP / PEO composite solid electrolyte membrane of the present invention comprises the following steps:

[0008] S1. Using urea as a raw material, two-stage pyrolysis is performed to obtain graphite carbon nitride g-CN, the g-CN is mixed and ground with metal cobalt powder, and high-temperature roasting is performed under the protection of an inert atmosphere. The product is soaked and washed with dilute hydrochloric acid, washed with water to neutrality after being taken out, and dried to obtain a cobalt-graphite carbon nitride composite material CNC;

[0009] S2, dispersing CNC in ethylene glycol to obtain a uniform suspension, adding nickel salt and phthalocyanine precursor to the suspension, adding ammonium molybdate as a catalyst, adding CTAB as a dispersant, stirring at room temperature, transferring to a high-pressure reactor for a solvothermal reaction, cooling after the reaction, separating the precipitate, washing the precipitate with anhydrous ethanol and deionized water, and drying to obtain a dry powder;

[0010] S3, soaking the dry powder in concentrated sulfuric acid for sulfonation treatment, separating it after sulfonation, washing it with water until it is neutral, and drying it to obtain CNF-supported sulfonated nickel phthalocyanine filler SCNC (SO3H-NiPc@CNC);

[0011] S4, dissolving polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP in dimethyl sulfoxide, adding lithium salt and filler SCNC prepared in step S3, stirring to obtain a viscous liquid, converting the viscous liquid into a membrane material by electrospinning or electrostatic spraying technology, and drying to obtain a PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler;

[0012] S5. Fully dissolve PEO and lithium salt in acetonitrile solvent at a molar ratio of EO:Li=10:1, stir evenly to obtain a casting solution, pour the casting solution on the three-dimensional fiber skeleton prepared in S4, dry it at room temperature, and obtain a modified PVDF-HFP / PEO composite solid electrolyte membrane, which can also be used as a diaphragm for lithium-ion batteries.

[0013] According to a preferred embodiment of the present invention, in S1, the conditions for preparing g-CN by two-stage pyrolysis using urea as a raw material are as follows: the first stage: in an inert atmosphere (high-purity nitrogen or argon) or a vacuum environment, the urea is heated to 540-560°C at a heating rate of 4-6°C / min, kept warm for 3-5h, and then cooled to room temperature; the second stage: in an inert atmosphere or a vacuum environment, the urea is heated to 490-510°C at a heating rate of 4-6°C / min, kept warm for 1.5-3h, and then cooled to room temperature to obtain graphite carbon nitride g-CN.

[0014] The first stage of pyrolysis: urea will undergo pyrolysis reaction to produce preliminary graphitic carbon nitride.

[0015] The second stage pyrolysis: further improve the crystallinity and stability of graphitic carbon nitride.

[0016] According to a preferred embodiment of the present invention, in S1, graphite carbon nitride g-CN and metal cobalt powder are mixed and ground in a mass ratio of 1:1, and heated to 750-850°C at a heating rate of 1.5-3°C / min under an inert atmosphere (high-purity nitrogen or argon), and kept warm for 1.5-3h; after the insulation is completed, cool to room temperature, take out, soak the product in dilute hydrochloric acid overnight, take out, wash with water until neutral, and dry to obtain CNC.

[0017] According to a preferred embodiment of the present invention, in S2, CNC is dispersed in ethylene glycol to obtain a suspension with a dispersion concentration of 8-12wt%, and a nickel salt and a phthalocyanine precursor are added to the suspension, wherein the mass ratio of CNC to nickel element is 8-10:1 according to the mass of nickel element; the phthalocyanine precursor is 4-aminophthalonitrile, and the mass ratio of CNC to nickel element is 12:1; the mass ratio of 4-aminophthalonitrile to ammonium molybdate is 7-8:1; and the concentration of CTAB added to the reaction system is 0.3-0.4g / L.

[0018] According to a preferred embodiment of the present invention, in S2, the solvothermal reaction conditions are: solvothermal reaction at 160-165° C. for 8-12 hours.

[0019] According to a preferred embodiment of the present invention, in S3, the dry powder is soaked in 98% concentrated sulfuric acid for 6-12 hours, separated, washed with deionized water until neutral, and fully dried to obtain sulfonated nickel phthalocyanine filler SCNC.

[0020] According to a preferred embodiment of the present invention, in S4, PVDF-HFP is first dissolved in dimethyl sulfoxide to obtain a 150-250 g / L solution, and then lithium salt and filler SCNC prepared in step S3 are added, wherein the mass ratio of PVDF-HFP to filler SCNC is 200:2-5.

[0021] According to a preferred embodiment of the present invention, in S4, the lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4, LiAsF6 and LiDFOB; the mass ratio of the lithium salt to PVDF-HFP is 1-3:4.

[0022] According to a preferred embodiment of the present invention, in S5, the lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4, LiAsF6 and LiDFOB; wherein the molecular weight of PEO is generally between 100,000 and 1,000,000. wherein the molar ratio of EO to lithium salt in PEO is 10:1.

[0023] An appropriate proportion of lithium salt can provide sufficient carriers (i.e., lithium ions) to ensure that the electrolyte has good ionic conductivity. If the lithium salt content is too low, it may not be enough to form an effective ion transport path; conversely, if the lithium salt content is too high, it may lead to increased crystallinity, which in turn reduces ionic conductivity. This ratio of EO:Li ratio helps maintain the mechanical integrity of the electrolyte material and form a stable SEI layer, which is crucial to preventing corrosion of electrode materials and extending battery life. Too high or too low a lithium salt ratio may lead to lithium salt precipitation or excessive local concentration, which in turn affects the overall performance of the electrolyte.

[0024] In a second aspect, the present invention provides a modified PVDF-HFP / PEO composite solid electrolyte membrane, which is prepared by the preparation method of any one of the above embodiments.

[0025] (III) Beneficial effects

[0026] The technical effects of the present invention include the following aspects:

[0027] (1) PVDF-HFP is electrospun or electrostatically sprayed to obtain a PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler, and the three-dimensional fiber skeleton is used to compound with PEO-LiTFSI casting solution to obtain a solid electrolyte membrane (diaphragm), and the high ionic conductivity of PVDF-HFP is improved by using the high ionic conductivity of PVDF-HFP. The three-dimensional fiber skeleton is an electrospinning / electrostatic spraying fiber structure. As a three-dimensional skeleton of the solid electrolyte membrane, it can construct a long-range ordered 3D lithium ion transmission channel, effectively improving the ionic conductivity of the diaphragm. At the same time, the PVDF-HFP three-dimensional skeleton can improve the mechanical strength and stability of the PEO-based solid electrolyte membrane to a certain extent, buffer the volume change during the electrochemical reaction, improve the ability of the solid electrolyte membrane to resist the growth of lithium dendrites, enhance its compatibility with the lithium anode, and improve the electrochemical performance of the battery under high voltage.

[0028] (2) The present invention also adds sulfonated nickel phthalocyanine filler SCNC to the PVDF-HFP three-dimensional fiber skeleton. The interaction between the active sites of the nickel phthalocyanine filler and the PVDF-HFP chain increases the amorphous region of the polymer and improves the conductivity of lithium ions. The presence of conjugated π-π bonds within the entire nickel phthalocyanine filler molecule leads to a high dielectric response, inducing a strong solubility for lithium ions, promoting the dissociation of lithium salts and improving the mobility of lithium ions. The dense metal centers (M) in NiPc have stronger polarity than H atoms, inducing the dissociation of lithium salt anions (TFSI). - ) has strong chemical adsorption capacity, improving Li + Transfer number (t Li+ ).

[0029] (3) When preparing the sulfonated nickel phthalocyanine filler SCNC, the growth of nickel phthalocyanine NiPc is based on the pre-prepared cobalt-graphite carbon nitride composite material CNC, and the nickel salt and phthalocyanine precursor are in situ synthesized on the CNC. The phthalocyanine precursor is anchored by the active sites on the CNC, which can greatly improve the dispersibility of nickel phthalocyanine NiPc and effectively avoid the agglomeration of NiPc. At the same time, the π-π conjugated stacking effect formed by nickel phthalocyanine NiPc and CNC can promote the dissociation of lithium salt to produce more Li + And provide a fast transmission path for radial ion diffusion. Through sulfonation treatment, SO3H groups are introduced on nickel phthalocyanine NiPc, which can improve the strong chemical adsorption capacity for lithium salt anions (TFSI-) and promote the dissociation and transmission of lithium salts.

[0030] (4) Compared with the unmodified PEO solid electrolyte membrane, the present invention can effectively improve the operating voltage window of the electrolyte membrane (reaching 4.8V); compared with the PEO solid electrolyte membrane modified only with PVDF, the present invention can significantly improve the tensile strength of the electrolyte membrane (reaching 6.1MPa) by using the PVDF-HFP three-dimensional skeleton. Compared with the unmodified PEO solid electrolyte membrane (ionic conductivity is about 1.5*10 -4 S / cm), the ionic conductivity of the electrolyte membrane of the present invention can reach 1.77×10- 3 S / cm (60℃), the conductivity is greatly improved compared with the existing technology.

[0031] The modified PEO solid electrolyte membrane of the present invention complements SO3H-NiPc@CNC filler, 3DPVDF-HFP skeleton and PEO. The three can synergistically complement each other while retaining their own advantages, so that the ionic conductivity, mechanical strength and stability of the finally prepared modified PEO-based solid electrolyte membrane are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the SEM image of the sulfonated nickel phthalocyanine filler SCNC prepared in step (3) of Example 1.

[0033] Figure 2 This is the SEM image of the PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler prepared in step (4) of Example 1.

[0034] Figure 3 This is a photo of the modified PVDF-HFP / PEO composite solid electrolyte membrane prepared in step (5) of Example 1.

[0035] Figure 4 The oxidative decomposition potential test results of lithium-solid electrolyte-stainless steel button batteries assembled with three modified solid electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0036] Figure 5 These are the tensile test results of three modified solid electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0037] Figure 6 The lithium plating stripping test results of lithium-button cells assembled with three modified solid electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0038] Figure 7 Polarization curves of lithium-solid electrolyte-lithium button cells assembled with three modified solid electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0039] Figure 8 Electrochemical impedance spectroscopy (EIS) of lithium-solid electrolyte-lithium button cells assembled with three modified solid electrolyte membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0040] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0041] Example 1

[0042] The present invention provides a method for preparing a modified PVDF-HFP / PEO composite solid electrolyte membrane, the steps of which are as follows:

[0043] (1) Put 45g of urea in a crucible and place it in a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, keep it warm for 4h, and after it cools to room temperature, heat it to 500℃ at the same heating rate and keep it warm for 2h to complete the secondary heat treatment to obtain graphite carbon nitride (g-CN). Mix graphite carbon nitride and metal cobalt powder in a ratio of 1:1 and grind them, put them in a ceramic ark and place them in a tube furnace, heat them to 800℃ at a heating rate of 2℃ / min under nitrogen protection, and keep them warm for 2h. After cooling to room temperature, take it out, soak the obtained powder in hydrochloric acid for 12h to wash away the unreacted cobalt powder, and wash it with deionized water until it is neutral, and dry it at 60℃ for 16h to obtain cobalt-graphite carbon nitride composite material CNC.

[0044] (2) Take 0.03g of CNC prepared in the previous step and disperse it in ethylene glycol, stir and ultrasonically treat it to obtain a CNC suspension with a dispersion concentration of 10wt%. Add 0.014g of nickel chloride hexahydrate and 0.036g of 4-aminophthalonitrile (phthalocyanine precursor) to the CNC suspension, add 0.005g of ammonium molybdate as a catalyst, add 0.005g of CTAB (hexadecyltrimethylammonium bromide), stir at room temperature for 30min, transfer the reaction system to a reactor, react at 160℃ by solvent thermal method for 10h, cool, separate the precipitate, wash the precipitate with anhydrous ethanol and deionized water, and dry it to obtain a dry powder, which is a nickel phthalocyanine@CNC composite material.

[0045] (3) The nickel phthalocyanine@CNC composite material was immersed in 98% sulfuric acid for sulfonation for 10 hours, washed with deionized water several times, and dried at 60°C for 12 hours to obtain SO3H-NiPc@CNC filler (i.e., SCNC filler).

[0046] like Figure 1 The figure shows the SEM image of SO3H-NiPc@CNC filler observed under a 20K scanning electron microscope. It can be seen from the figure that the particle size of SO3H-NiPc@CNC filler is uniform, about 1.5μm, and the surface is rough, which can provide more active sites. It helps to form a stable structure in the composite material, ensuring good compatibility and dispersibility. In addition, the rough surface structure not only increases the contact area between the filler and the matrix, but also promotes Li + transport sites, thus improving the electrochemical activity.

[0047] (4) Take 2 g of PVDF-HFP and fully dissolve it in 10 mL of dimethyl sulfoxide solvent, add 0.03 g of the SCNC filler prepared in step (3) and 0.9 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), stir for 12 h to obtain a viscous solution, electrospin the solution, and then put it into a vacuum drying oven at 60 ° C for 12 h to obtain a PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler.

[0048] like Figure 2As shown in the figure, it is a SEM image of PVDF-HFP three-dimensional fiber skeleton observed under a 20K scanning electron microscope. It can be observed from the figure that the PVDF-HFP three-dimensional fiber skeleton is a criss-crossed fiber-like multilayer network structure, the fiber diameter is evenly distributed, and several intersections are formed between the fibers. The fibers are interlaced between the layers, and SCNC particles are distributed in the network structure. These intersections and staggered fiber arrangement not only improve the structural stability of the material, but also enhance the material's resistance to mechanical stress. Combined with the presence of SCNC particles, this network structure can also enhance the responsiveness to ion concentration gradients, improve the battery's charge and discharge performance, and lay the foundation for the application of efficient and stable solid-state lithium-ion batteries. This special structure can construct a long-range ordered 3D lithium ion transmission channel, effectively improve the ion conductivity of the diaphragm, improve the mechanical strength and stability of the PEO-based solid electrolyte membrane, buffer the volume change during the electrochemical reaction, improve the ability of the solid electrolyte membrane to resist the growth of lithium dendrites, and enhance its compatibility with the lithium anode.

[0049] (5) Take 4.4 g of PEO and 1.891 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) (wherein the molar ratio of EO:Li=10:1) and fully dissolve them in 100 mL of acetonitrile solvent, stir for 12 h to obtain a uniform viscous solution, pour the viscous solution on the three-dimensional fiber skeleton prepared in step (3), and dry it at room temperature for 24 h to obtain the modified PVDF-HFP / PEO composite solid electrolyte membrane of this embodiment.

[0050] like Figure 3 As shown, the picture of the modified PVDF-HFP / PEO composite solid electrolyte membrane prepared in this embodiment has a flat surface without wrinkles. It shows that the membrane has good uniformity and consistency during the preparation process, which is crucial for improving the ionic conductivity of the electrolyte. The flat surface also contributes to good contact between battery components, reduces interfacial impedance, and thus optimizes the overall performance of the battery. In addition, the wrinkle-free property of the membrane can effectively reduce stress concentration, improve the mechanical strength and stability of the membrane, and ensure that it maintains good morphology and function during battery operation. These superior surface properties provide strong support for the effectiveness of the composite solid electrolyte membrane in high energy density and high power applications.

[0051] Comparative Example 1

[0052] This comparative example is based on Example 1, except that the SCNC nanofiller added to the PEO solution during the preparation process is replaced with an equal amount of CNC. According to the method of Example 1, a solid polymer electrolyte membrane with a thickness of 110 μm is prepared, which is marked as PPLC.

[0053] The modified PVDF-HFP / PEO composite solid electrolyte membrane (PVDF-HFP / SO3H-NiPc@CNC / PEO / LiTFSI) prepared in Example 1 was tested to have a thickness of about 110 μm, an electrochemical window of 4.8 V, and an ionic conductivity of 3.1*10 -4 S / cm, and the ionic conductivity at 60°C is 1.77×10- 3 Under the same test conditions, the CNC-modified PEO solid electrolyte membrane (thickness of about 110 μm) prepared in Comparative Example 1 has an ionic conductivity of 1.5*10 -4 S / cm, and the electrochemical window is 4.45V.

[0054] Example 2

[0055] The present invention provides a method for preparing a modified PVDF-HFP / PEO composite solid electrolyte membrane, the steps of which are as follows:

[0056] (1) Put 45g of urea in a crucible and place it in a muffle furnace, heat it to 560℃ at a heating rate of 6℃ / min, keep it warm for 3h, and after it cools to room temperature, heat it to 510℃ at the same heating rate and keep it warm for 3h to complete the secondary heat treatment to obtain graphite carbon nitride (g-CN). Mix graphite carbon nitride and metal cobalt powder in a ratio of 1:1 and grind them, put them in a ceramic ark and place them in a tube furnace, heat them to 850℃ at a heating rate of 3℃ / min under nitrogen protection, and keep them warm for 2.5h. After cooling to room temperature, take it out, soak the obtained powder in hydrochloric acid for 12h to wash away the unreacted cobalt powder, and wash it with deionized water until it is neutral, and dry it at 60℃ for 16h to obtain cobalt-graphite carbon nitride composite material CNC.

[0057] (2) Take 0.04g CNC prepared in the previous step and disperse it in ethylene glycol, stir and ultrasonically treat it to obtain a CNC suspension with a dispersion concentration of 12wt%. Add 0.017g nickel chloride hexahydrate and 0.050g 4-aminophthalonitrile (phthalocyanine precursor) to the CNC suspension, add 0.006g ammonium molybdate as a catalyst, add 0.005g CTAB (hexadecyltrimethylammonium bromide), stir at room temperature for 30min, transfer the reaction system to a reactor, react at 165℃ by solvent thermal method for 8h, cool, separate the precipitate, wash the precipitate with anhydrous ethanol and deionized water, and dry it to obtain a dry powder, which is a nickel phthalocyanine@CNC composite material.

[0058] (3) The nickel phthalocyanine@CNC composite material was immersed in 98% sulfuric acid for sulfonation for 12 hours, washed with deionized water several times, and dried at 60°C for 12 hours to obtain SO3H-NiPc@CNC filler (i.e., SCNC filler).

[0059] (4) Take 2 g of PVDF-HFP and fully dissolve it in 10 mL of dimethyl sulfoxide solvent, add 0.04 g of the SCNC filler prepared in step (3) and 1.0 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), stir for 12 h to obtain a viscous solution, electrospin the solution, and then place it in a vacuum drying oven at 60 ° C for 12 h to obtain a PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler.

[0060] (5) Take 4.4 g of PEO and 1.891 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) (wherein the molar ratio of EO:Li=10:1) and fully dissolve them in 100 mL of acetonitrile solvent, stir for 12 h to obtain a uniform viscous solution, pour the viscous solution on the three-dimensional fiber skeleton prepared in step (3), and dry it at room temperature for 24 h to obtain the modified PVDF-HFP / PEO composite solid electrolyte membrane of this embodiment.

[0061] Comparative Example 2

[0062] This comparative example is based on Example 2, except that the SCNC nanofiller added to the PEO solution during the preparation process is replaced with an equal amount of NC. According to the method of Example 2, a solid polymer electrolyte membrane with a thickness of 110 μm is prepared, which is marked as PPLNC.

[0063] The modified PVDF-HFP / PEO composite solid electrolyte membrane (PVDF-HFP / SO3H-NiPc@CNC / PEO / LiTFSI) prepared in Example 2 was tested to have a thickness of about 110 μm, an electrochemical window of 4.87 V, and an ionic conductivity of 3.3*10 -4 S / cm, and the ionic conductivity at 60°C is 1.83×10 -3 Under the same test conditions, the PVDF-modified PEO composite solid electrolyte membrane (thickness of about 110 μm) prepared in Comparative Example 2 has an ionic conductivity of 1.67*10 -4 S / cm, and the electrochemical window is 4.52V.

[0064] At the same time, the tensile strength of the PVDF-modified PEO composite solid electrolyte membrane prepared in Comparative Example 2 is 3MPa, while the tensile strength of the modified PVDF-HFP / PEO composite solid electrolyte membrane prepared in Example 2 reaches 6.1MPa. The composite electrolyte membrane prepared in Example 2 of the present invention has a significant enhancement in mechanical strength, improving its ability to resist the growth of lithium dendrites. When the composite electrolyte membrane prepared in this example is used as a diaphragm of a solid-state battery, the safety of the battery can be improved.

[0065] Electrochemical performance test:

[0066] Test 1: The SCNC-modified PEO solid polymer electrolyte membrane PPLSNC prepared in Example 1, the CNC-modified PEO solid polymer electrolyte membrane PPLC prepared in Comparative Example 1 and the NC-modified solid electrolyte PPLNC assembled lithium-solid electrolyte-stainless steel button cells were tested for oxidative decomposition potential. The test results are shown in Figure 4 As shown. Figure 4 It can be seen from the oxidation potential analysis that the oxidation potential of the CNC-modified PEO solid electrolyte PPLC is only 4.45V. Under the same modified filler addition amount, the oxidation potential of the NC-modified PEO electrolyte PPLNC is 4.52V, while the oxidation potential of the SCNC-modified PEO electrolyte PPLSNC can reach 4.8V. This shows that the electrolyte membrane PPLSNC has better antioxidant ability, making the solid electrolyte membrane more compatible with high-voltage electrodes.

[0067] Test 2: The tensile test was performed on the SCNC-modified PEO solid polymer electrolyte membrane PPLSNC prepared in Example 1, the CNC-modified PEO solid polymer electrolyte membrane PPLC prepared in Comparative Example 1, and the NC-modified solid electrolyte PPLNC prepared in Comparative Example 2. The test results are shown in Figure 5 As shown. Figure 5 It can be seen that with the addition of SCNC, the mechanical strength of PPLSNC (6.1MPa) is significantly enhanced compared with PPLNC (6MPa) and PPLC (5.5MPa), and the deformation of PPLSNC (165%) is also enhanced compared with PPLNC (144%) and PPLC (130%), which shows that the PEO solid polymer electrolyte modified by PPLSNC has better tensile strength and mechanical properties. This is mainly because the introduction of sulfonic acid groups enhances the interaction between polymer chains and forms more hydrogen bonds, which effectively improves the flexibility of polymer chains. During the stretching process, this flexibility enables the material to better adapt to strain, thereby improving the tensile fracture strength. At the same time, the presence of sulfonic acid groups can enhance the mobility between polymer segments. The free movement of the chain segments enables the molecular chains to slide and rearrange better when the material is stretched, which reduces stress concentration and helps the ductility of the material. As a result, the SCNC-modified PEO solid polymer electrolyte of the present invention has excellent mechanical properties compared to CNC- and NC-modified PEO solid polymer electrolytes, and is very suitable for manufacturing all-solid-state batteries that meet various special shapes and design requirements.

[0068] Test 3: Lithium plating stripping test was performed on the lithium-button cell assembled with the SCNC-modified PEO solid polymer electrolyte membrane PPLSNC prepared in Example 1, the CNC-modified PEO solid polymer electrolyte membrane PPLC prepared in Comparative Example 1, and the NC-modified solid electrolyte PPLNC prepared in Comparative Example 2. The test was conducted using a blue electric system, and the test results are shown in Figure 6 As shown. Figure 6 It can be seen that the Li / PPLNC / Li symmetric battery exhibits an extremely unstable overpotential, and a short circuit occurs after 130 hours of cycling. In contrast, the initial polarization voltage in PPLNC is too large, and it cannot maintain a stable cycle. The polarization voltage increases again at 420 hours, and a short circuit occurs at 591 hours. Under the same test conditions, the Li / PPLSNC / Li symmetric battery can be stably cycled for more than 1500 hours without a short circuit, and maintains a stable voltage gap (36mV) during the test. This shows that the introduction of sulfonated nickel phthalocyanine improves the ionic conductivity of the electrolyte, which means that lithium ions can be transported more smoothly through the electrolyte. This improvement can improve the overall performance and cycle stability of the battery, thereby reducing the risk of battery failure during long-term cycling.

[0069] Test 4: A polarization test was performed on the lithium-solid electrolyte-lithium button cell assembled with the SCNC-modified PEO solid polymer electrolyte membrane PPLSNC prepared in Example 1, the CNC-modified PEO solid polymer electrolyte membrane PPLC prepared in Comparative Example 1, and the NC-modified solid electrolyte PPLNC prepared in Comparative Example 2. Figure 7 The polarization curve is shown in Figure 2. The polarization method is: the number of lithium ion transfers when the excitation voltage is 10mV. The initial current of the electrolyte membrane PPLSNC is 0.29μA. As the polarization time goes by, it reaches stability at around 200s, and the steady-state current is 0.22μA.

[0070] Further testing of the impedance of each electrolyte membrane before and after polarization yielded the following results: Figure 8 According to the electrochemical impedance spectrum (EIS), the electrolyte membrane PPLSNC prepared in Example 1 (polarization time is 1000s) has an impedance of 81Ω before polarization and 75Ω after polarization, and the impedance decreases by 6Ω after polarization. The calculated lithium ion transfer number of the electrolyte membrane MNPL reaches 0.75. In contrast, the lithium ion migration numbers of PPLNC of Comparative Example 2 and PPLC of Comparative Example 1 are 0.73 and 0.68, respectively, indicating that the electrolyte membrane PPLSNC prepared in Example 1 of the present invention has a strong lithium ion transport capacity.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a modified PVDF-HFP / PEO composite solid electrolyte membrane, characterized in that: The following steps are included: S1. Using urea as a raw material, two-stage pyrolysis is performed to obtain graphite carbon nitride g-CN, the g-CN is mixed and ground with metal cobalt powder, and high-temperature roasting is performed under the protection of an inert atmosphere. The product is soaked and washed with dilute hydrochloric acid, washed with water to neutrality after being taken out, and dried to obtain a cobalt-graphite carbon nitride composite material CNC; S2, dispersing CNC in ethylene glycol to obtain a uniform suspension, adding nickel salt and phthalocyanine precursor to the suspension, adding ammonium molybdate as a catalyst, adding CTAB as a dispersant, stirring at room temperature, transferring to a high-pressure reactor for a solvothermal reaction, cooling after the reaction, separating the precipitate, washing the precipitate with anhydrous ethanol and deionized water, and drying to obtain a dry powder; S3, soaking the dry powder in concentrated sulfuric acid for sulfonation treatment, separating it after the sulfonation, washing it with water until it is neutral, and drying it to obtain CNC-loaded sulfonated nickel phthalocyanine filler SCNC; S4, dissolving polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP in dimethyl sulfoxide, adding lithium salt and filler SCNC prepared in step S3, stirring to obtain a viscous liquid, converting the viscous liquid into a membrane material by electrospinning or electrostatic spraying technology, and drying to obtain a PVDF-HFP three-dimensional fiber skeleton doped with SCNC filler; S5. Fully dissolve PEO and lithium salt in acetonitrile solvent at a molar ratio of EO:Li=10:1, stir evenly to obtain a casting solution, pour the casting solution on the three-dimensional fiber skeleton prepared in S4, dry at room temperature, and obtain a modified PVDF-HFP / PEO composite solid electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: In S1, the conditions for preparing g-CN by two-stage pyrolysis using urea as raw material are as follows: the first stage: in an inert atmosphere or a vacuum environment, the urea is heated to 540-560°C at a heating rate of 4-6°C / min, kept warm for 3-5h, and then cooled to room temperature; the second stage: in an inert atmosphere or a vacuum environment, the urea is heated to 490-510°C at a heating rate of 4-6°C / min, kept warm for 1.5-3h, and then cooled to room temperature to obtain graphitic carbon nitride g-CN.

3. The preparation method according to claim 1, characterized in that: In S1, graphite carbon nitride g-CN and metal cobalt powder are mixed and ground in a mass ratio of 1:1, and heated to 750-850°C at a heating rate of 1.5-3°C / min under an inert atmosphere, and kept warm for 1.5-3h; after the insulation is completed, it is cooled to room temperature, taken out, and the product is soaked in dilute hydrochloric acid overnight, taken out, washed with water until neutral, and dried to obtain CNC.

4. The preparation method according to claim 1, characterized in that: In S2, CNC is dispersed in ethylene glycol to obtain a suspension with a dispersion concentration of 8-12wt%, and nickel salt and phthalocyanine precursor are added to the suspension, wherein the mass ratio of CNC to nickel element is 8-10:1 based on the mass of nickel element; the phthalocyanine precursor is 4-aminophthalonitrile, and the mass ratio of CNC to nickel element is 12:1; the mass ratio of 4-aminophthalonitrile to ammonium molybdate is 7-8:1; and the concentration of CTAB added to the reaction system is 0.3-0.4g / L.

5. The preparation method according to claim 1, characterized in that: In S2, the solvothermal reaction conditions are: solvothermal reaction at 160-165°C for 8-12 hours.

6. The preparation method according to claim 1, characterized in that: In S3, the dry powder is soaked in 98% concentrated sulfuric acid for 6-12 hours, separated, washed with deionized water until neutral, and fully dried to obtain sulfonated nickel phthalocyanine filler SCNC.

7. The preparation method according to claim 1, characterized in that: In S4, PVDF-HFP is first dissolved in dimethyl sulfoxide to obtain a 150-250 g / L solution, and then lithium salt and the filler SCNC prepared in step S3 are added, wherein the mass ratio of PVDF-HFP to the filler SCNC is 200:2-5.

8. The preparation method according to claim 1, characterized in that: In S4, the lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4, LiAsF6 and LiDFOB; the mass ratio of the lithium salt to PVDF-HFP is 1-3:

4.

9. The preparation method according to claim 1, characterized in that: In S5, the lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4, LiAsF6 and LiDFOB; wherein the molecular weight of PEO is 100,000 to 1,000,000.

10. A modified PVDF-HFP / PEO composite solid electrolyte membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polymer electrolyte membrane preparation method and solid-state battery

    CN116247291A

  • An aqueous solid electrolyte slurry, a solid electrolyte membrane, and a secondary battery

    CN116365054B

Cited By

  • PVDF-HFP-based composite solid electrolyte and electrolyte membrane synergistically optimized by ionic liquid and F127, and preparation method and application of PVDF-HFP-based composite solid electrolyte and electrolyte membrane

    CN121484188A

  • A method for modifying and dispersing Al2O3 filler in a PVDF-HFP composite solid electrolyte.

    CN122659294A